2016
DOI: 10.1103/physrevd.93.115040
|View full text |Cite
|
Sign up to set email alerts
|

Minimal vectorlike leptonic dark matter and signatures at the LHC

Abstract: We propose a minimal vector-like leptonic dark matter (DM) with renormalisable interaction in a beyond the Standard Model (SM) scenario, where the SM is augmented with a vector-like doublet and a singlet leptons. The additional fermions are odd under a discrete Z2 symmetry, while the rest of the SM particles are singlets, and thus providing stability to the DM. In this scenario, we show that, the DM emerges as an admixture of the neutral component of the vector-like doublet and the singlet leptons. The singlet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 86 publications
(78 reference statements)
0
48
0
Order By: Relevance
“…The detailed study of collider signature for vector-like fermions can be found in [32,36,37,41]. As we have already seen, due to the presence of the second Higgs doublet large sin θ can be achieved satisfying both relic density and direct detection.…”
Section: Collider Phenomenologymentioning
confidence: 97%
See 1 more Smart Citation
“…The detailed study of collider signature for vector-like fermions can be found in [32,36,37,41]. As we have already seen, due to the presence of the second Higgs doublet large sin θ can be achieved satisfying both relic density and direct detection.…”
Section: Collider Phenomenologymentioning
confidence: 97%
“…As a consequence, smaller mixing should give rise to smaller σ SI , making the DM parameter space more viable from direct search bound. The presence of the second Higgs helps in keeping the VLF mixing within a moderate limit, unlike the case in [32] where the bound on the mixing is even more stringent due to the presence of only one (SM) Higgs. This is a consequence of sin 2 α m 2 H suppression due to the heavier Higgs and small scalar mixing in case of scalar-mediated elastic scattering.…”
Section: B Direct Detection Of the Dark Mattermentioning
confidence: 99%
“…In the most stringent case for a large mixing sin β ∼ 0.66, one gets |M N 2 −M N 1 | < 250 GeV. In the opposite case of a small mixing sin β < 0.1, |M N 2 − M E | is restricted to be less than a few GeV [39]. In our numerical analysis we will always work with a small β and assume N 2 , E are degenerate.…”
Section: Jhep05(2016)030mentioning
confidence: 99%
“…For light N 2 , the decays h → N 1N2 /N 2N1 , N 2N2 and Z → N 1N2 /N 2N1 , N 2N2 may also be allowed. These decay modes could provide more severe constraints [39], but are still weaker than the LUX constraint. Therefore we will not consider invisible decays as an individual constraint in our later analysis.…”
Section: Analysis Of Parameter Spacementioning
confidence: 99%
See 1 more Smart Citation